Code-Switching as a Sociolinguistic Marker in EFL Classroom Interaction - Yen Polisda (STBA Prayoga Padang, 2015)
Code-switching is a language alternation used by students speaking English as second or foreign language in communication. It is effectively used to create a communicative interaction in natural settings of foreign language, that is, classroom settings in Indonesia. However, Indonesian teachers teaching English consider switching codes as language competence failure. This study proved that using Indonesian while expressing ideas in English was effectively used to meet sociolinguistic functions- equivalence, floor-holding, reiteration, and conflict control. In addition, it was a communicative strategy used by EFL learners to overcome communication difficulties to achieve an intended communication. Therefore, this paper places a great importance of utilizing code-switching for classroom interaction for beginners as proved by this study. By the findings of this study, it is expected that code-switching is not considered as a communicative competence failure in learning English as a foreign language, but as communication strategy a continuity of the speech.